My brother Sam is dead - Collier, James Lincoln; Collier, Christopher 1930- (New York Scholastic, Inc., 1974)
Recounts the tragedy that strikes the Meeker family during the Revolution when one son joins the rebel forces while the rest of the family tries to stay neutral in a Tory town.
770L
71159.
Keywords: United States -- History -- Juvenile fiction. -- Revolution, 1775-1783; Historical fiction